FRI0285 Sensitivity To Change of Nailfold Videocapillaroscopy and Relationship with Disease Progression. (15th July 2016) - Avouac, J.; Toniolo, E.; Lepri, G.; Hurabielle, C.; Vallet, A.; Allanore, Y.
Abstract : Background: Nailfold videocapillaroscopy (NVC) is a simple, non-invasive and inexpensive imaging technique that allows a detailed assessment of skin microcirculation. Although NVC has face and content validity for the detection of microvascular damages related to systemic sclerosis (SSc), its sensitivity to change has not been assessed in detail. Objectives: Our aim was to determine in a prospective cohort the merit of NVC to detect meaningful changes over time and whether these changes are associated with disease progression. Methods: A prospective cohort of 140 SSc patients was recruited over a 12-month period and was followed up on an annual basis for 3 years. NVC was performed at inclusion and repeated once a year by four investigators (ET, GL, CH and AV) according to a standardized procedure. NVC pictures were analysed by one investigator (JA) and classified as early, active and late patterns. Organ progression was defined according to validated definitions. The worsening of the Medsger severity scale (from category 1–2 to category 3–4) was considered as a marker of disease progression. Results: 140 SSc patients were included (111 women, 56±11 year-old, disease duration of 9±8 years). A change of NVC pattern was observed in 29 SSc patients (21%) during the follow-up period.At least 3 annual NVC evaluations were available for each patient. A progression from a normal or early NVC pattern to an active NVC pattern was detected in 15 patients (10%). Patients who progressed to the active NVC pattern were significantly less at risk to develop ischemic digital ulcers (DU) during follow-up (hazard ratio, HR: 0.78, 95% Confidence Interval, CI 0.17–0.95). A progression to a late NVC pattern was observed in 14 patients (10%). Progression to a late NVC pattern was associated with the occurrence of new ischemic DU (HR: 4.51, 95% CI 1.68–12.14), lung vascular progression (HR: 5.12 95% CI 1.23–21.27), progression of skin fibrosis (HR: 3.70, 95% CI 1.14–11.94) and the worsening of Medsger disease severity scale (HR: 4.47, 95% CI 1.63–12.26). Conclusions: Change of the NVC pattern was observed in 21% of patient with SSc during a follow-up of 3 years. NVC has the ability to detect meaningful changes over time associated with markers of disease progression. Our results support the use of NVC for the routine follow-up of SSc patients in order to improve their risk stratification. NVC might be used in the future to select high-risk patients and change to a late NVC pattern might be regarded as potential surrogate marker for disease severity. Disclosure of Interest: None declared